Analisis Kualitas Pelayanan dalam Pengelolaan Fasilitas di Stasiun Kereta Api Gubeng Surabaya - Rheina Dwi Qurani Anggraini; Intan Kusumaningayu; Ir. Benny Bintarjo Dwi Hersanjo (Jurnal Lingkungan Karya Arsitektur, 2025)
The Gubeng Surabaya Class A Train Station is one of the main transportation hubs in the city of Surabaya. However, the facilities provided at this station still face various challenges that affect passenger comfort and service efficiency. The primary issues include accessibility for people with disabilities, inadequate pedestrian facilities, limited parking capacity, and inconsistencies in staff services.This study employs data collection methods through interviews with passengers at Gubeng Station. The collected data were systematically processed to identify deficiencies in each aspect of the facilities and services. The findings reveal that although Gubeng Station has provided basic facilities, significant improvements are still needed. For example, ramps and guiding blocks for people with disabilities are not yet fully ideal, especially in the drop-off area, restroom access, and platforms. Pedestrian facilities are poorly organized, causing confusion and additional costs for passengers. Parking areas are often insufficient, particularly during peak hours, resulting in inconvenience for private vehicle users. Moreover, while staff services are generally deemed adequate, some shortcomings remain in providing comfort and security. In conclusion, although Gubeng Station has made efforts to offer adequate facilities, further improvements are required to ensure better comfort, efficiency, and accessibility for all passengers. This study recommends upgrading facilities and providing staff training to enhance the quality of service in the future.